Peran Kepemimpinan Dalam Meningkatkan Disiplin Karyawan Pada PT. Perkebunan Nusantara III Medan - Bayu Rahmat Hidayat; Muhammad Irwan Padli Nasution (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research aims to identify and explain the role of leadership in improving employee discipline at PT. Perkebunan Nusantara III Medan. In carrying out this research, researchers used a qualitative descriptive research type. This research uses a special method that aims to explain specific phenomena in depth and data collection techniques are carried out by observation or observation so that researchers immediately go into the field to obtain data that can really be trusted. The results of the study show that the role of leadership has a major influence in increasing employee discipline. Because the leader becomes the most dominant person and has authority, power in all efforts to create employee work discipline.